Performance of wheat genotypes in two environments in the State of São Paulo - Junior, Edivaldo José Ferreira (2013)
Twenty genotypes of wheat were compared in experiments carried out under rainfed conditions and acid soil in Capão Bonito, SP, Brazil, and spray irrigation conditions and lime amended soil in Tatuí, SP, in 2007. Grain yield, aluminum tolerance in nutrient solutions in the laboratory and other agronomic traits were analyzed. Line 6, tolerant to Al3 + toxicity, stood out in terms of grain yield, with semi-dwarf plants and resistance to lodging in Capão Bonito. In Tatuí, line 18 showed higher grain yield, and all genotypes were semidwarf plants, with lines 3 and 20 being resistant to lodging. As for crown-rust, lines 12, 16, 17 and 20 were immune for both experiments. The most productive genotypes under rainfed conditions and acid soil were those tolerant to aluminum toxicity in nutrient solutions.